A comparison of selected OnLAC year 6 and year 7 longitudinal results for 10-15 year olds in care - Flynn, Robert; Miller, Meagan (Université d'Ottawa | University of Ottawa, 2009)
Presented at the 2009 Ontario Looking After Children Data Review Day
Keywords: child welfare; outcome monitoring; longitudinal; onlac; ontario looking after children